Expressão do Grb10 durante o crescimento folicular em bovinos - Bohrer, Rodrigo Camponogara (2011)
The growth factor receptor-bound protein 10 (Grb10) has been extensively studied in human and has been implicated in the regulation of MAPK and PI3K pathways, activated by Insulin-like Growth Factor Receptor (IGF-IR). In cattle, it is well established that the IGF system is required for follicular dominance. On the other hand, Grb10 protein has not been studied in follicular development, dominance or deviation of any species. Then, we conducted experiments to characterize the Grb10 in ovarian follicular cells and to evaluate the regulation of Grb10 mRNA expression during follicular deviation. Cow ovaries were obtained from an abattoir, transported to the laboratory on ice and processed immediately. Granulosa and theca cells collected from follicles of 3-5 mm, 6-8 mm and > 8 mm of diameter expressed Grb10 mRNA and protein. Western blot assay from granulosa cells lysates showed a single band while three bands were observed in theca cells. The confocal study demonstrated presence of Grb10 in the cytoplasm of theca and granulosa cells. After characterize the Grb10 message and protein in follicular cells, we studied the regulation of Grb10 in follicular cells during deviation in vivo. Higher Grb10 mRNA expression was observed in subordinate follicles when compared to the dominant follicle (P < 0.05) as well as a negative correlation between Grb10 and aromatase throughout the follicular deviation (P < 0.05). To our knowledge, this is the first report of Grb10 expression in granulosa and theca cells during follicular development. Moreover, the results present strong evidence that Grb10 mRNA expression is regulated during follicle deviation and, therefore, is potentially involved in the selection of dominant follicle in cattle.